PLACEMENT OF COMPETENT AND QUALIFIED EDUCATION PERSONNELS FOR INCREASING HIGHER EDUCATION QUALITY - Kartika, Ika; Nisa, Zakia Hary; Karlina, Haura; Umronih, Dewi (Jurnal Visi Ilmu Pendidikan, 2023)
Educational human resources comprise of administrators, teachers, and support personnel. Educators are frequently overlooked in educational administration.  This study aimed to assess the impact of STIKes B's implementation of educational staff administration for the sound quality of education. This research used descriptive qualitative research methodologies. Data collection techniques include interviews, observation, and documentation. The results indicated that the management of educators and education personnel at the stages of planning, selection, orientation, appointment and placement, observation and assessment, compensation, and dismissal had been implemented, but not to the greatest extent possible. There are educators and educational personnel who lack the requisite expertise. The offered compensation is regarded as meager. Good human resource planning, providing educational human resource support, and human resource development through training, certification, observation, and equitable compensation are required to enhance the quality of education personnel.